2020
DOI: 10.1002/cmdc.202000430
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Suitable Peptidic Molecular Platform for the Development of NPY(Y1)R‐Specific Imaging Agents

Abstract: NPY(Y1)R (neuropeptide Y receptor subtype 1) is an important target structure for tumor‐specific imaging and therapy as this receptor subtype is overexpressed in very high density and incidence especially in human breast cancer. Targeting this receptor with radiolabeled truncated analogues of the endogenous ligand NPY (neuropeptide Y) has, however, not yet resulted in satisfactory imaging results when using positron emission tomography (PET). This can be attributed to the limited stability of these PET imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…42c), 280 and very recently in the synthesis of a disulfide containing, truncated neuropeptide Y (NPY) analogue. 281 5.10.13 Sec-isoamyl mercaptan (SIT) and 2-methyloxolane-3-thiol (MOT). 3-Methyl-2-butanethiol/sec-isoamyl mercaptan (SIT, Fig.…”
Section: Benzyloxymethyl (Bom)mentioning
confidence: 99%
“…42c), 280 and very recently in the synthesis of a disulfide containing, truncated neuropeptide Y (NPY) analogue. 281 5.10.13 Sec-isoamyl mercaptan (SIT) and 2-methyloxolane-3-thiol (MOT). 3-Methyl-2-butanethiol/sec-isoamyl mercaptan (SIT, Fig.…”
Section: Benzyloxymethyl (Bom)mentioning
confidence: 99%
“…Recently, Krieger et al have reported the synthesis of 68 Ga-radiolabeled analogues of the most promising previously described truncated NPY analogues and compared them regarding their metabolic stability [133]. Of the nearly 80 truncated peptides analogues of NPY that have been developed over the years, the authors chose the following five by virtue of their metabolic stability: linear [Pro 30 ,Lys(DOTA) 31 ,Tyr 32 68 Ga 3+ (which was obtained by the fractioned elution of an IGG 68 Ge/ 68 Ga generator system) in an aqueous acetate-buffered solution.…”
Section: Npy Y1 Receptormentioning
confidence: 99%